Fintech platforms: Lax or careful borrowers' screening? - Serena Gallo (Financial Innovation, 2021)
Can peer-to-peer lending platforms mitigate fraudulent behaviors? Or have lending players been acting similar to free-riders? This paper constructs a new proxy to investigate lending platform misconduct and compares the FICO score and the LendingClub credit grade. To examine whether the lack of verification by the Fintech platform affects lenders' collection performance, I explore the recovery rate (RR) of non-performing loans through a mixed-continuous model. The regression results show that the degree of prudence taken by the lending platform in the pre-screening activity negatively affects the detection of some misreporting borrowers. I also find that the Fintech platform's missing verification information (e.g., annual income and employment length) affects the RR of non-performing loans, thereby hampering lenders' collection performance.
Keywords: 650; Credit grade; Misconduct; Misreporting; Peer to peer lending; Recovery rate